MANAGEMENT ISSUES IN SERVICE SECTOR (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The nature of services, their organizational features and specificities of the service market make this sector difficult to manage and pose a number of problems for managers of enterprises in the sector and require a differentiated management approach. The scientific article discusses a number of problems of the management of enterprises in the service sector, such as management of demand and supply, inventory management and service quality management. Completing the available theoretical information on the above-mentioned problems, we have presented the correlations between them and our views on the solution of these problems. We have presented our conclusions regarding the requirements for the management system of service sector enterprises. Also, our approaches to solving the described problems were presented. The article was summarized with appropriate conclusions, completing the options for possible solutions to the problems we have studied.
Keywords: service; service management; demand and supply management; inventory management; risk management; quality management